THE OBLIGATION OF MAINTENANCE AS AN ALIMONY RIGHT IN CIVIL LAW AND ITS IMPLICATIONS IN INDONESIA - Indah Imelda Pramesti; I Dewa Ayu Dwi Mayasari (INTELIGENSIA MEDIA, 2026)
Alimentary rights are a form of legal protection aimed at ensuring the fulfillment of living needs for those entitled, such as wives and children, within the context of family relationships. In Indonesian civil law, the obligation to provide support as alimentary rights is grounded in the Indonesian Civil Code (KUHPerdata) and the Marriage Law No. 1 of 1974. This study aims to analyze the concept of support obligations within the framework of alimentary rights and their implications, particularly in divorce cases. Using a normative juridical approach, this research examines legislation and court decisions related to the implementation of alimentary rights. The findings indicate that alimentary rights serve not only to meet material needs but also reflect legal and moral responsibilities to protect the welfare of children and former spouses. However, the implementation of these obligations faces challenges, including weak law enforcement, low public legal awareness, and financial constraints of the obligated party. Necessary solutions include strengthening regulations, increasing legal education for the public, and optimizing mechanisms for monitoring and law enforcement. With these steps, alimentary rights as part of the support obligations can be effectively implemented and offer optimal protection for all entitled parties